Survival Rate of Hepatocellular Carcinoma Patients with Varying Individual Characteristics: A Retrospective Cohort Study - Mardhiyah, Imalatul; Masrizal, Masrizal; Pradipta, Yudi; Novirsa, Randy; Soko, Wilson (UNIVERSITAS ALIFAH PADANG, 2025)
Background: There is a continuous demand for an integrated survival analysis that takes into account clinical biomarkers and socio-demographic factors in Hepatocellular carcinoma (HCC) patients from Southeast Asia. This study figured out the mortality predictors that were independent of HCC patients at a major tertiary referral center in Indonesia.Methods: This retrospective cohort study looked into 123 HCC patients who were admitted to Dr. M. Djamil General Hospital, Padang (2018-2023). These patients were selected by simple random sampling. Survival analysis was conducted using Kaplan-Meier curves, log-rank tests, and multivariate Cox regression.Results: Median survival was 284 days with mortality at 24.4%. Univariate analysis showed that albumin <3.5 g/dL (HR=7.67, p=0.045), AFP ≥20 ng/mL (HR=2.16, p=0.044), age ≥59 years (HR=2.38, p=0.018), and obesity (HR=3.43, p=0.013) were significantly associated factors. Multivariate Cox regression indicated that AFP level was the leading factor (adjusted HR=3.94, 95%CI: 1.67-9.33, p=0.002), followed by age ≥59 years (adjusted HR=3.52, p=0.002) and education (adjusted HR=0.36, p=0.014).Conclusions: AFP level, old age, and education were the independent factors of HCC deaths in Central Sumatra. Besides, the conjunction of clinical and socio-demographic factors may be utilized for prognostic risk stratification to pinpoint the most at-risk groups and hence direct the targeted interventions that are most compatible with resource-limited settings predominately HBV-related HCC.